Improving fever management of hospitalized children with cancer: barriers, facilitators, and proposed interventions from healthcare providers in Kenya - Kisembe, Everlyn; Nessle, C. Nathan; Dettinger, Julia; Nyamusi, Lenah; Kinja, Sarah; Ndung’u, Mercy; Langat, Sandra; Busby, Kenneth; Olbara, Gilbert; Vik, Terry A.; Moyer, Cheryl A.; Njuguna, Festus (Frontiers in Oncology, 2025)
Children with cancer in lower-middle-income countries (LMICs) are at increased risk of dying from infections. Prompt treatment of fever episodes improves outcomes, yet poorly described challenges impair management. This qualitative study explored healthcare provider perspectives on barriers to and facilitators of inpatient fever management in children with cancer at a public tertiary referral children’s hospital in Kenya. Healthcare providers involved in fever management were recruited. Semi-structured interviews were audio-recorded, transcribed verbatim, and entered into NVivo software. Coding was informed by a theoretical fever framework and the Consolidated Framework for Implementation Research. Thematic analysis and mind mapping identified recurrent themes and subthemes. Strategies were mapped to identified barriers. The sixteen participants included nurses (n = 2), clinicians (n = 6), pharmacists (n = 2), phlebotomists (n = 2), and microbiology laboratory staff (n = 4). We identified three overarching themes: empowerment of healthcare providers and caregivers, the importance of timely management, and teamwork/human resource availability. Healthcare provider attributes served as facilitators: motivation to improve care, eagerness to learn, willingness to change practice, and need for treatment guidance. Factors within the hospital system were barriers, with subthemes including poor communication between cadres, delays in laboratory results, and staffing shortages. Participants suggested knowledge sharing, a treatment guideline, task shifting, and hiring additional healthcare providers as potential interventions. Managing fever episodes in children with cancer is complex, requiring multiple cadres of healthcare providers and caregiver participation. The proposed interventions may overcome barriers, but future studies are needed to assess the effectiveness of these strategies in improving fever management.